PENGARUH KECERDASAN EMOSI TERHADAP PRESTASI AKADEMIK SISWA SMA PEMBANGUNAN PADANG - Tasya Syifa Nabila; Gladys Julia Berin; Ririn Julia; Aisha Nabila Khairunnisa; Azira Lesti Octavia; Izzanil Hidayati (Sindoro: Cendikia Pendidikan, 2024)
This study aims to analyze the influence of emotional intelligence on the academic performance of high school students at SMA Pembangunan. Using a quantitative method with a correlational approach, the study involved 50 students selected through probability sampling. Data were collected using questionnaires designed to measure aspects of emotional intelligence, such as self-awareness, self-regulation, motivation, empathy, and social skills, as well as students' academic performance. Data analysis was conducted using Pearson correlation to determine the relationship between the two variables. The results showed that emotional intelligence has a positive and significant effect on academic performance. These findings highlight the importance of developing emotional intelligence as an integral part of education to support students' academic success. This study contributes to the development of a more holistic educational approach, focusing not only on cognitive aspects but also on students' emotional well-being.